Mixed Eucalyptus plantations in subtropical China enhance phosphorus accumulation and transformation in soil aggregates - Cui, Yuhong; Yan, Yu; Wang, Shengqiang; Zhang, Han; He, Yaqin; Jiang, Chenyang; Fan, Rongyuan; Ye, Shaoming (Frontiers in Forests and Global Change, 2023)
Introduction The production of Eucalyptus, a principal economic tree genus in China, is faced with challenges related to soil phosphorus (P) limitations. In this study, we explore variations in phosphorus content, storage, and transformation in Eucalyptus forests. We hypothesize that mixed forests augment soil aggregate stability and P content and that microaggregates are pivotal in determining P differences between mixed and pure forests. Additionally, we posit that mixed forests foster P transformation, enhancing its efficacy in the soil. Current research on the distribution and transformation of soil total P (TP) and P fractions at the soil aggregate level is limited. Methods In this study, we selected soil from a Eucalyptus-Mytilaria laosensis Lecomte mixed forest, Eucalyptus-Erythrophleum fordii Oliv mixed forest, and pure Eucalyptus forest in Chongzuo County, Guangxi, China, as the research objects. Using a dry-sieving method, we divided the soil collected in situ from the 0–40 cm layer into aggregates of >2, 1–2, 0.25–1, and <0.25 mm particle sizes, measured the TP and P fractions (resin-extractable inorganic P, bicarbonate-extractable inorganic P, bicarbonate-extractable organic P, sodium hydroxide-extractable inorganic P, sodium hydroxide-extractable organic P, dilute hydrochloric acid-extractable P, concentrated hydrochloric acid extractable inorganic P, concentrated hydrochloric acid-extractable organic P and residue-P) in different aggregates, and used redundancy analysis and PLS SEM to reveal key factors affecting soil P accumulation and transformation. Results The results showed that compared to pure Eucalyptus forests, mixed Eucalyptus forests significantly enhanced the stability of soil aggregates and the content and storage of phosphorus, especially the Eucalyptus-Mytilaria laosensis mixed forest. The content of total soil phosphorus and its fractions decreased with increasing aggregate particle size, while the opposite trend was observed for stored P, with aggregates <0.25 mm being the main fraction influencing soil phosphorus accumulation. The transformation process of P fractions was primarily constrained by dissolution rates, mineralization rates, biological activity, including the action of microbes, fungi, and plant–root interactions, and other factors. Discussion Mixed forests increased the transformation of phosphorus in soil aggregates, effectivel enhancing the availability of soil phosphorus. In summary, this study provides important evidence for the systematic management of subtropical artificia Eucalyptus forests and the sustainable utilization of soil resources.